The Added Value of Baseline Health-Related Quality of Life in Predicting Survival in High-Risk Prostate Cancer Patients Following Radical Prostatectomy. Issue 5 (5th November 2022) - Westhofen, Thilo; Buchner, Alexander; Kasivisvanathan, Veeru; Lennartz, Simon; Schlenker, Boris; Becker, Armin; Stief, Christian G.; Kretschmer, Alexander
Abstract : Purpose: Several studies have shown baseline health-related quality of life to be a valuable prognostic indicator of survival outcomes for various cancer entities in the metastatic setting. To date, there is no evidence regarding the prognostic value of baseline health-related quality of life for patients undergoing radical prostatectomy due to localized prostate cancer. Materials and Methods: A total of 1, 029 patients with high-risk prostate cancer according to National Comprehensive Cancer Network® risk stratification and prospectively assessed baseline health-related quality of life prior to radical prostatectomy were identified. Patients were stratified by global health status domain of the QLQ-C30 questionnaire. Oncologic endpoints were biochemical recurrence-free survival and metastasis-free survival. Multivariable Cox regression models were performed to assess prognostic significance of baseline global health status on survival outcomes. Harrell's discrimination C-index was applied to calculate the predictive accuracy of the model and previously described risk stratification models. Decision curve analysis was applied to test the clinical net benefit associated with adding global health status to our multivariable model ( P < .05). Results: Median follow-up was 43 months. In multivariable analysis, global health status was confirmed as an independent predictor for increased biochemical recurrence-free survival (HR .97, 95% CI .96-.99; P = .001) and metastasis-free survival (HR .96, 95% CI .93-.99; P = .013), indicating a relative risk reduction of 2.9% for biochemical recurrence-free survival and 3.7% for metastasis-free survival per 1-point increase of baseline global health status. Adding baseline health-related quality of life to our model and to the Cancer of the Prostate Risk Assessment and National Comprehensive Cancer Network score improved discrimination in predicting biochemical recurrence-free survival and metastasis-free survival of the respective models. Decision curve analysis revealed a net benefit over all threshold probabilities. Conclusions: Our findings highlight baseline health-related quality of life to be a valuable and robust prognostic factor for patients with localized high-risk prostate cancer prior to radical prostatectomy. Baseline health-related quality of life increased prognostic accuracy of biochemical recurrence-free survival and metastasis-free survival.